Estudos de comunicação no Brasil: uma análise dos programas de pós-graduação, docentes, teses e dissertações - Silva, Gabriel Resende da (2023)
It is a challenge for the knowledge areas to understand their own characteristics, roles in the field of education, and prospects for scientific research considering the changes over the decades, which is a need in the field of Communication. As the object of study to achieve visibility regarding the historical development and the current scenario of the field, postgraduate programs were chosen because they have been strong drivers for the development and consolidation of the Communication field in Brazil. Through a temporal cut - from 2013 to 2020 - an exploratory descriptive analysis, of a qualitative-quantitative nature, was carried out using the open data repository of CAPES and the Brazilian Digital Library of Theses and Dissertations. To apply the necessary treatments and generate analyses of the chosen databases, the KDD process (Knowledge Discovery in Databases) was chosen, which enables obtaining knowledge from large databases using data mining techniques through computational solutions for summarization, categorization, or data classification. The tools used for data mining were Iramuteq and PowerBI Desktop. The results reveal a significant concentration of programs in the Southeast region of the country, a focus on academic education, years in which the creation of programs was significant when compared to other years, and that the majority of faculty members hold doctoral degrees and have predominantly permanent professional affiliations. Regarding the theses and dissertations, it was possible to identify thematic classes that concentrate discussions on communication from the perspective of cinema, media, and technology. For each of the identified thematic classes, a greater presence of higher education institutions such as PUC São Paulo in the study of image, UFSM in the study of informational vehicles, and Metodista in the study of information could be observed.